Spotlight on COP29: scaling up private climate finance in developing countries - Popovic,I (Imperial Grantham Institute, 2024)
Key points•Scaling up climate finance for developing countries will be at the forefront of discussions at the next annual climate talks, COP29.•Most investments in climate solutions are concentrated in developed countries, with only a small proportion reaching least developed and developing countries. •While investments in climate mitigation and adaptation are growing, a significant gap remains between current finance and what is needed to meet Paris Agreement goals.•Mobilising private finance, alongside scaling up public finance, is essential to closing this funding gap and ensuring that finance reaches those most in need.•Boosting private investments in developing countries requires: a coordinated effort between public and private sectors; supportive policies; diverse financial instruments; and stronger engagement from international financial institutions.